Orofaciodigital syndrome with mesomelic limb shortening. Issue 3 (June 1984) - Burn, J; Dezateux, C; Hall, C M; Baraitser, M
Abstract : Two sisters, the children of first cousin Pakistani Moslem parents, have unusual facies, tongue hamartomata, pre- and postaxial polydactyly, severe talipes, and mesomelic limb shortening associated with tibial dysplasia. Homozygosity for a recessive gene defect is probable. The phenotype resembles, but is distinct from, the orofaciodigital syndromes delineated to date. We suggest that this condition be labelled OFD IV.